The Role of Quercetin in Alleviating the Testicular Oxidative Stress and Apoptosis in Streptozotocin-Induced Diabetes - Hajiyeva, Ramila; Durmuş, Sinem; Tunçdemir, Matem; Gelişgen, Remise; Sözer, Volkan; Büyükçolpan Mirzataş, Eda; Şimsek, Gönül; Uzun, Hafize (Cerrahpaşa Medical Journal, 2021)
Objective: The aim of this study was to investigate the effects of quercetin on oxidative stress and apoptosis in testicular tissue of streptozotocin- induced diabetic male rats. Methods: Thirty-two Wistar type Albino rats were divided into 4 groups. The groups are planned as follows: group 1: control group (only 0.9% sodium chloride, i.p. injection for 30 days, n = 8), group 2: DM group (streptozotocin: 50 mg/kg, freshly dissolved in 0.9% sodium chloride, i.p, n = 8), group 3: DM + QR group (quercetin: 20 mg/kg/day, diluted in 4% ethanol, 30 days, i.p.) (streptozotocin: 50 mg/kg, i.p., single dose, n = 8), group 4: control + QR group (quercetin: 20 mg/kg/day, 30 day, i.p., n = 8). Testicular tissue samples were taken under anesthesia on the 31st day of the study. Malondialdehyde, lipid hydroperoxide, advanced oxidation protein products, total thiol, nonprotein sulfhydryl compounds, and Cu,Zn-superoxide dismutase were determined by spectrophotometric method. Results: Malondialdehyde and lipid hydroperoxide levels were higher in the DM group compared to the control and DM + QR group. Advanced oxidation protein product levels were lower in the control group than in the control + QR and DM group, while total thiol, nonprotein sulfhydryl levels, and Cu,Zn-superoxide dismutase activity were higher in DM + QR group compared to control and DM groups. In the DM + QR group, a significant decrease was found in the number of apoptotic cells compared to the DM group (P < .001). Conclusion: Quercetin administration can be potentially beneficial and effective in preventing oxidative stress (lipid and protein) damage and apoptosis in the testicles of diabetic rats. Cite this article as: Hajiyeva R, Durmuş S, Tunçdemir M, et al. The role of quercetin in alleviating the testicular oxidative stress and apoptosis in streptozotocin-induced diabetes. Cerrahpaşa Med J. 45(3):159-166.